Genome characterization, pathogenicity, and evaluation of therapeutics of Klebsiella aerogenes in Bombyx larvae infection model - Tansha Kabir; Md. Ismail Hossain; Tangerul A. Jepu; Mrinmoy Sarker; Nusrat U. A. Saleh; Hafsa Monir; Nafisa Nawaar; Sadia A. Jene; Md Mahtab Hossain; M. Aftab Uddin; M. Latiful Bari; Muktadir S. Hossain (BMC Microbiology)
Abstract Antibiotic resistance against human pathogenic bacteria is a global problem and the issue is becoming increasingly serious. Klebsiella aerogenes, a Gram-negative pathogen, is usually found in soil and water, but there are increasing number of reports in on isolation of antibiotic-resistant strains of it. Here, we report the draft genome of a food-borne Klebsiella aerogenes strain isolated from street food of Dhaka, Bangladesh. The WGS analysis revealed the presence of a number of virulence genes and antibiotic-resistance genes. Using the infection model of the larvae of the silk moth, Bombyx mori, we show that the K. aerogenes strain killed larvae within 72 h of injection into the hemolymph (blood) or midgut. Although the strain showed resistance to ampicillin in vitro among the antibiotics tested, it showed sensitivity to ampicillin in vivo in Bombyx larvae. Direct injection of aqueous extracts of hog plum or Indian gooseberry into the midgut of larvae infected with K. aerogenes increased larval survival rate to ~ 75% after 72 h. These results indicate that Bombyx larvae could be used to carry out in vivo screening of plant extracts with potential therapeutic effects against pathogenic bacteria like K. aerogenes.